Polycarbonate based multifunctional self-sensing 2D and 3D printed structures for aeronautic applications. (12th July 2021) - Costa, P; Dios, J R; Cardoso, J; Campo, J J; Tubio, C R; Gonçalves, B F; Castro, N; Lanceros-Méndez, S
Abstract: Different polycarbonate materials have been reinforced with carbon nanotubes to tune electrical conductivity and to induce piezoresistive self-sensing capabilities. Further, the composites were processed by solvent casting and fused deposition modelling (filament for 3D printing) methods. An electrical conductivity percolation threshold of ≍0.3 wt.% has been found for solvent casted films, whereas samples processed by 3D printing show higher thresholds, ≍2 wt.%, presenting all samples a similar maximum electrical conductivity ( σ ≍ 1 × 10 −3 S m −1 ), thermal and chemical properties. Overall mechanical properties are larger for the solvent cast films concerning the 3D printed ones, particularly the elongation at break. The piezoresistive sensitivity, obtained after four-point-bending and uniaxial strain experiments, shows gauge factors up to 1.7, independently of the processing method. The functionality of the materials has been demonstrated by the implementation of an airplane wing section model with self-sensing capabilities. Two implemented strategies showed the suitability of the developed materials for real-time monitoring of the wing mechanical deformation.